Activation and suppression of 〈c + a〉 dislocations in a textured Mg–3Al–1Zn alloy. (1st April 2020) - Zhao, Dexin; Ma, Xiaolong; Picak, Sezer; Karaman, Ibrahim; Xie, Kelvin
Abstract: In this work, we statistically studied the activation and suppression of 〈 c  +  a 〉 dislocations in a textured Mg–3Al–1Zn alloy after compression. Our results revealed that the activation and suppression of 〈 c  +  a 〉 dislocations in polycrystals are primarily governed by the overall texture, regardless of the crystallographic orientation of each grain. This observation is explained by the requirement of five independent slip systems, reduced anisotropy, and twin-induced strain localization. These direct observations of 〈 c  +  a 〉 dislocation activities offer a key insight into understanding the deformation mechanism of polycrystalline Mg alloys. Graphical abstract: Image, graphical abstract